Alternative Punishment as a Suitable Alternative to Imprisonment - Lešková, Lýdia; Haburajová Ilavská, Lenka; García Martín, José (Journal of Education Culture and Society, 2022)
Aim. The philosophy of alternative punishment is based on keeping the convicted person free, while imposing a punishment that will act preventively against committing another felony. The paper focuses on perceiving the importance of alternative punishment as part of restorative justice, and on presenting the results of the questionnaire survey which aimed to identify the public´s preferences in the context of various forms of alternative punishments as an option, instead of imprisonment. Attention is paid to three alternative punishments, specifically: community service, house arrest, and monetary sentence (fine).Methods. The questionnaire survey aimed to find out what forms of alternative punishment are, according to the respondents, a suitable alternative to incarceration. The survey sample comprised of Slovak individuals (N=1078) aged from 16 years and older, thereof 31.3% men (N=337) and 68.7% women (N=741).Results. Based on the analysis of the data collected from the 1078 respondents´ answers to the individual questions in the questionnaire, community service was identified as the most favorable alternative to imprisonment, whereas the least preferences the respondents gave to the option of monetary fines.Conclusion. The concept of alternative punishment is understood as a form of punishment that fulfills the purpose of a sentence, without deprivation of freedom, but still guaranteeing the fulfilment of a court-ordered unconditional retribution. Compared to traditional forms of punishment, alternative methods of resolving judicial cases do not enforce repression and prefer the individual approach to punishing the accused (convicted) persons with emphasis on corrective aspects of alternative punishment. The results of the survey showed that the respondents strongly prefer one form of alternative punishment, namely the community service.